Enhanced electrical properties in solution-processed InGaZnO thin-film transistors by viable hydroxyl group transfer process. (28th March 2018) - Kim, Do-Kyung; Jeong, Hyeon-Seok; Kwon, Hyeok Bin; Kim, Young-Rae; Kang, Shin-Won; Bae, Jin-Hyuk
Abstract: We propose a simple hydroxyl group transfer method to improve the electrical characteristics of solution-processed amorphous InGaZnO (IGZO) thin-film transistors (TFTs). Tuned poly(dimethylsiloxane) elastomer, which has a hydroxyl group as a terminal chemical group, was adhered temporarily to an IGZO thin-film during the solidification step to transfer and supply sufficient hydroxyl groups to the IGZO thin-film. The transferred hydroxyl groups led to efficient hydrolysis and condensation reactions, resulting in a denser metal–oxygen–metal network being achieved in the IGZO thin-film compared to the conventional IGZO thin-film. In addition, it was confirmed that there was no morphological deformation, including to the film thickness and surface roughness. The hydroxyl group transferred IGZO based TFTs exhibited enhanced electrical properties (field-effect mobility of 2.21 cm 2 V −1 s −1, and on/off current ratio of 10 6 ) compared to conventional IGZO TFTs (field-effect mobility of 0.73 cm 2 V −1 s −1 and on/off current ratio of 10 5 ).